The extent of the hip bone sexual dimorphism in two Italian coeval modern skeletal samples - Rita Sorrentino; Annalisa Pietrobelli; Davide Mameli; Teresa Nicolosi; Maria Giovanna Belcastro (Scientific Reports)
Abstract The rate of sexual dimorphism in the human hip bone is primarily due to the structural demands of childbirth. Genetic, environmental, and socio-cultural factors can also influence pelvic shape variations across populations. This study examines intra-population sex variation within the Italian population based on regional differences of 280 coxal bones from two documented human osteological collections (Bologna and Sassari) coming from different geographical areas, the northern continental and island regions. Nineteen metric variables were used to evaluate sexual dimorphism and population differences. Most of the variables showed sexual dimorphism, particularly the hip height and ischio-pubic measures within both populations, and accurately predicted sex for each population (Bologna: 100%; Sassari: 91.2%). Results show the Bologna sample have larger dimensions for most of the measurements than the Sassari one, especially when considering the longitudinal ones. Some female traits of the Bologna sample are larger than the correspondent ones in the Sassari males. The rate of sexual dimorphism between the populations shows significant differences, with better sex distinction for Bologna than Sassari. This study aims at interpreting these intra-population differences, considering the effect of environmental (physical and social milieu) and genetic factors, underscoring the importance of this local differences for accurate diagnostic criteria.